Impact of eccentricity and depth-to-breadth ratio on the behavior of skirt foundation rested on dry gypseous soil - Abd-Alhameed Hind Jamal; Albusoda Bushra Suhale (Journal of the Mechanical Behavior of Materials, 2022)
Gypseous soils are considered one of the most problematic soils. The skirted foundation is an alternative technology that works to improve the bearing capacity and reduce settlement. This paper investigates the use of square skirted foundations resting on gypseous soil subjected to concentric and eccentric vertical load with eccentricity values of 4, 8, and 17 mm in 16 experimental model tests. To obtain the results by using this type of foundation, a small-scale physical model was designed to obtain the load–settlement behavior of the square skirted foundation; the dimension of the square footing is 100 mm × 100 mm with 1 mm thickness, the skirt depth (D s) was 0.5, 1, and 1.5B (where B is the footing width). The footing rests on dry gypseous soil with a relative density of 33%. The tests show that the gypsum content of the soil is 59%. The result shows that the highest bearing capacity for the square shape footing with D s/B = 1.5 subjected to concentric load results in an improvement ratio of 190%. For the eccentric load, with D s/B = 1.5, the increase in bearing capacity is about 120% at e = 8 mm when compared with using a foundation without a skirt.